HUBUNGAN ANTARA USIA, PARITAS, PEKERJAAN DAN INDEK MASSA TUBUH DENGAN KEJADIAN PROLAP ORGAN PANGGUL BERDASARKAN SKOR PELVIC ORGAN PROLAPSE QUANTIFICATION - Ermawati Ermawati; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2018)
Pelvic organ prolapse is a condition that affects the quality of women life. Pelvic organ prolapse can be caused by injury until the birth process, the aging process, the composition of the tissue in a woman, a chronic cough, or often do heavy work. Early detection of prolapse associated with Prognosis of anatomy and functional pelvic organs recovery. So we need training and learning more about Pelvic Organ Prolapse Quantification (POPQ) are clearly. The study was conducted by the method of case control study in the department of OB polyclinic of Dr. M. Djamil Padang Hospital from September 2013 until the total sample of 98 patients with 49 control groups and 49 in the case group. Analyzes were connected to assess the association of age, parity, occupation and body mass index with the incidence of pelvic organs prolapse based on POPQ. Score data are presented in tabular form. Data were tested by t-test and chi square test. If p <0.05 indicates significant results. There is a significant relationship between age and the incidence of pelvic organ prolapse (p <0.05) and OR 27,871. there is a significant correlation between parity and the incidence of pelvic organ prolapse (p<0.05) and OR 52,970. From the statistical analysis of the work, it cannot be tested statistically. From the body mass index, there is no significant relationship to the occurrence of pelvic organ prolapse (P> 0.05) and OR 1:00.Keywords: age, parity, occupation, body mass index, pelvic organs prolapse